First episode psychosis with and without the use of cannabis and synthetic cannabinoids: Psychopathology, global functioning and suicidal ideation - Ricci, Valerio; Ceci, Franca; Di Carlo, Francesco; Di Muzio, Ilenia; Ciavoni, Laura; Santangelo, Monica; Di Salvo, Gabriele; Pettorruso, Mauro; Martinotti, Giovanni; Maina, Giuseppe (Psychiatry research, 2023)
•Users of natural cannabinoids, of synthetic cannabinoids and non-users were included.•Psychotic symptoms, dissociation and suicidality were compared during a nine-months follow-up.•More severe positive symptoms were found in synthetic cannabinoids users.•Suicidal ideation was found to be higher among those using synthetic cannabinoids.•Despite the small sample-size, the study provide insights into the role of cannabinoids in psychoses. Natural Cannabis (NC) and Synthetic Cannabinoids (SCs) use can increase the risk of developing psychotic disorders and exacerbate their course. To examine the differences between psychoses not associated with cannabis use and those associated with NC and SCs use, evaluating psychotic symptoms, global functioning, dissociative symptoms and suicidal ideation. The sample of 61 patients with First Episode Psychosis (FEP) was divided into 3 groups: non-Cannabis users (non-users, N = 20); NC users (THC-users, N = 21); SCs users (SPICE-users, N = 20). Each group was assessed at FEP and after 3 and 9 months through specific psychopathological scales. THC-users, and even more SPICE-users, displayed much more severe positive symptoms than non-users. Negative symptoms were higher among non-users. After 9 months the non-users had recovered significantly better than SPICE-users in their global functioning. Dissociative symptoms were significantly greater in substance users. Finally, suicidal ideation was higher in SPICE-users than in both THC-users and non-users. The psychoses induced by NC and SCs showed different symptomatic pictures and outcomes from each other and when compared to the psychoses not associated with the use of substances; such knowledge could be relevant in identifying a specific drug treatment.